Peningkatan Motivasi Belajar Matematika Melalui Strategi Team Game Tournament Dengan Media Cartoon Game Pada Siswa Kelas 2 MI Muhammadiyah Program Khusus Kartasura Tahun Ajaran 2015/2016 - Fatoni, Fatkhul, Drs. Mulyadi, M.Pd (2016)
The purpose of the research is to increase the motivation to learn math by media Cartoon Game from the first cycle to the next cycle in grade 2 MI Muhammadiyah PK Kartasura in the academic year 2015/2016. Type of research is the PTK (Classroom Action Research). The subject of research is the teacher of mathematics grade 2 MI Muhammadiyah Special Programs Kartasura and student grade grade 2 MI Muhammadiyah Special Programs Kartasura totaling 30 students. This research carried out by two cycles where each cycle there are two meetings. The results showed an increase in motivation to learn mathematics, it is proved from the results of the data in cycle 1 meeting 1 on the participatory aspect 51.66%, 65.83% attention, enthusiastic 43.33%, 64.16% and pleasure. Data cycle 1 meeting 2 obtained data on the participatory aspect of 61.66%, 73.33% attention, enthusiastic 60.83%, 76.66% and pleasure. Data cycle 2 1 meeting on the participatory aspect 83.33%, 90.83% attention, enthusiastic 88.33%, 95.00% and pleasure. And data in cycle 2 2 meeting on the participatory aspect 96.66%, 98.33% attention, enthusiastic 97.50%, 99.16% and pleasure. It is concluded that with the implementation of the strategy with the media Tournament Team Game Cartoon Games can increase motivation to learn math in grade 2 in MI MuhammadiyahKartasura Special Program 2015/2016 Academic Year